PERFORMANCE EVALUATION OF A MASSIVE MIMO M-MMSE SYSTEM IN TERMS OF ENERGY EFFICIENCY BASED ON THE POWER CIRCUIT CONSUMPTION MODEL (PC) - Antsa Salomà El Salam Andriamihaja (International Journal of Innovations in Engineering Research and Technology, 2024)
The implementation of massive MIMO technology presents a significant boost in throughput mobile networks. However, this technological advancement comes increases energy consumption. The amalgamation of Massive MIMO with M-MMSE serves as a strategic solution, effectively mitigating energy consumption while delivering substantial throughput and improved Energy Efficiency (EE) compared to alternative techniques. Our study delves into the Energy Efficiency of massive MIMO using the Power Circuit Consumption (PC) model, providing valuable insights into its performance. This analytical approach not only enables a reduction in energy usage but also facilitates a noteworthy enhancement in Spectral efficiency (SE) and EE concurrently. This concurrent improvement addresses the challenge posed by the initial surge in energy consumption associated with massive MIMO deployment, ensuring a sustainable and efficient integration into mobile networks.